Capital structure and profitability of property firm in Malaysia / Nurul Nadiah Abdul Rahman - Abdul Rahman, Nurul Nadiah (Faculty of Business Management, 2017)
The aim of this report to go over the profitability and capital construction of property firms in Malaysia. By using secondary data, the empirical analysis of this study is confined to 6 property firms in Malaysia that listed on Bursa Malaysia with 11 year period of 2005 until 2015. Regarding to the study, the variables that be used returns on assets as a dependent variable, while total debt to equity, long term debt to equity, pre-tax profit margin and net profit margin as independent variables. The sources of these variables are from Datastream and the annual report of the property firms in Malaysia. This case of study using panel data, therefore the pool Ordinary Least Square (OLS) had been taken to determine the Coefficient of Determination (R-Squared), T-Test and F-Test to predict the relationship of the variables and to analyze the significant. It is found that all the independent variables which are totally debt to equity, long term debt to equity, pre-tax profit margin and net profit margin have a positive significant relationship to the return on asset as a dependent variable.